2021
DOI: 10.1093/humrep/deab088
|View full text |Cite
|
Sign up to set email alerts
|

Advanced trophectoderm quality increases the risk of a large for gestational age baby in single frozen-thawed blastocyst transfer cycles

Abstract: STUDY QUESTION Does trophectoderm (TE) quality affect birthweight after single frozen-thawed blastocyst transfer? SUMMARY ANSWER Transfer of single blastocyst with advanced TE quality was associated with higher birthweight and increased risk of a large for gestational age (LGA) baby. WHAT IS KNOWN ALREADY Transfer of blastocysts with advanced TE quality resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Therefore, we performed this retrospective cohort study that restricted maternal age and BMI to specific ranges ( 12 , 20 ) in a single tertiary academic medical center to investigate further the correlation between blastocyst quality, each morphologic characteristic, and a range of perinatal outcomes, including the incidence of PTD, the likelihood of a male neonate, birthweight and birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we performed this retrospective cohort study that restricted maternal age and BMI to specific ranges ( 12 , 20 ) in a single tertiary academic medical center to investigate further the correlation between blastocyst quality, each morphologic characteristic, and a range of perinatal outcomes, including the incidence of PTD, the likelihood of a male neonate, birthweight and birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…iDAScore did not correlate with basic neonatal outcomes such as malformation, birth weight, gestational age, and male sex rates. Previous studies suggested that blastocyst morphology, including the inner cell mass and trophectoderm, and morphokinetics correlate with sex [ 21 , 41 ], birthweight [ 42 , 43 ], and congenital anomalies [ 44 ]. However, the correlation between blastocyst quality and neonatal outcomes remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…BW differences have been shown before to be related to variations in growth trajectories emerging as early as the first trimester and continuing with greater EFW in the midtrimester 25 . Previous studies also showed the impact of both maternal cardiovascular profile and embryo quality on embryo/fetal growth, which we believe would be promising research areas 26,27 .…”
Section: Discussionmentioning
confidence: 54%
“…BW differences have been shown before to be related to variations in growth trajectories emerging as early as the first trimester and continuing with greater EFW in the midtrimester 25 . Previous studies also showed the impact of both maternal cardiovascular profile and embryo quality on embryo/fetal growth, which we believe would be promising research areas 26,27 . The choice of using the Hadlock formula 17 for calculation of EFW in our model was supported by the results of a previous study 28 , comparing 70 models of EFW extracted from 45 publications, in which it was deemed the most accurate model with the lowest Euclidean distance and highest proportion of absolute mean error ≤ 10%.…”
Section: Interpretation Of Findingsmentioning
confidence: 66%